Real-time in vivo Imaging of LPS-induced Local Inflammation and Drug Deposition in NF-κB Reporter Mice - Schmidtchen, Artur (Bio-Protocol, 2020)

(untitled) (Bio Protoc)
Wound, biomaterial, and surgical infections are all characterized by a localized and excessive inflammation, motivating the development of in vivo methods focused on the analysis of local immune events. However, current inflammation models, such as the commonly used in vivo models of endotoxin-induced inflammation are based on systemic, usually intraperitoneal, administration of lipopolysaccharide (LPS), causing endotoxin shock. Here, we describe a model of LPS-induced local inflammation in NF-κB-RE-Luc reporter mice. LPS, alone or with added therapeutic substances, is delivered locally via a hydrogel which is deposited subcutaneously, providing a spatially defined environment, enabling in vivo bioimaging analyses of local NF-κB activation. Evaluation of drug efficacy can be analyzed longitudinally in the same mouse, and using fluorescently labeled drugs, local drug deposition can be simultaneously analyzed, and correlated to the site of inflammation. Finally, the protocol can also be used to study retention and systemic release of the drug from locally deposited gels and other biomaterials.